Salinity stratification controlled productivity variation over 300 ky in the Bay of Bengal. Issue 1 (December 2017) - Silva, R.; Mazumdar, A.; Mapder, T.; Peketi, A.; Joshi, R.; Shaji, A.; Mahalakshmi, P.; Sawant, B.; Naik, B.; Carvalho, M.; Molletti, S.
Abstract The unique hydrographic setting of the Bay of Bengal (BoB) makes it an ideal tropical marine system to study the influence of regional and global forcings on productivity and [CO2aq ] through the late quaternary. Enormous fresh water flux into the BoB and consequent salinity stratification significantly weaken the convective mixing and wind driven processes which are commonly responsible for transport of nutrients to the euphotic zone driving primary productivity. Here we present a high resolution organic carbon-CaCO3 MAR and δ13 CTOC records for the last 300 ky from the BoB. The results show significant productivity variation at marine isotope sub-stages and millennial timescales. Colder sub-stages and stadials (Dansgard-Oeschger cycle) show a boost in productivity which may be attributed to thinning of low salinity cap, thereby facilitating efficient nutrient transport across the euphotic zone by the combination of wind driven processes (entrainment and upwelling), convective mixing and cold core eddies. The [CO2aq ] was a net result of global pCO2 variation and regional processes. Our long term high-resolution data indicates a possibility of marked change in productivity/biogeochemistry of BOB in the future due to global warming, thus affecting the coastal economy.